64.1k views
0 votes
Simplify the rational expressions. State any excluded values. Show your work. (3x - 6)/(x - 2)

2 Answers

3 votes
Hello,

Put the 3 as a common factor.

Look:

3x - 6 = 3 . ( x - 2 )

Then,

( 3x - 6) / (x - 2) = 3 .( x - 2) / (x -2)

Now simplity ( x -2)

= 3
User OmerN
by
6.5k points
2 votes

Answer:

3

Explanation:

We are given that a rational expression


(3x-6)/(x-2)

We have to simplify the rational expression.

To simplify the given expression we will take out common factor in numerator .


(3x-6)/(x-2)=(3(x-2))/(x-2)

Cancel out the same term in numerator and denominator . Then, we get


(3x-6)/(x-2)=3

Hence , the rational expression


(3x-6)/(x-2)=3

Answer:3

User Izzo
by
6.5k points